FTIR fingerprinting profiling, antioxidant activity, and α-glucosidase inhibitory activity of Orthosiphon stamineus leaf ethanolic extracts - Ahda, Mustofa; Jaswir, Irwandi; Khatib, Alfi; Ahmed, Qamar Uddin; Mahfudh, Nurkhasanah; Ardini, Yunita Dewi; Rohman, Abdul (2023)
Orthosiphon stamineus Benth (O. stamineus) leaves are herb plant parts that can act as an antioxidant and α-glucosidase inhibitor. Finding the best O. stamineus extract that serves as an antioxidant and α-glucosidase inhibitory agent is an essential requirement. Additionally, a clustering analysis based on FTIR spectra should be performed using principal component analysis (PCA) and partial least squares (PLS). Based on this study, the 40% ethanolic extract of O. stamineus leaves is a potent extract as an antioxidant and α-glucosidase inhibitory agent. Whereas 20% ethanolic extract of O. stamineus leaves is only applied as an α-glucosidase agent. Furthermore, discrimination analysis of O. stamineus leaf extracts showed that FTIR-based analysis can discriminate nicely each water, 60%, 80%, and 100% ethanolic extracts. This study reported that the obtained model has the determination coefficient of R2X: 0.991, R2Y: 0.964, and Q2Y: 0.946, which showed a good model and a good prediction. However, the classification method did not distinguish clearly between 20% and 40% ethanolic extracts. 20% ethanolic extract of O. stamineus leaves is always paired with 40% ethanolic extract of O. stamineus. Furthermore, several functional groups from O. stamineus leaf extracts contribute toward both biological activities including alkane groups, carbonyl groups, methylene groups, ester groups, and alkyl di-substitutions. Based on this study, quality control of potent extract as an antioxidant and as an α-Glucosidase Inhibitor should be conducted using a specific marker- based analysis.